PELATIHAN METODE TEMATIK DIGITAL QUR`Ä€N BAGI TUTOR PAI UPI UNTUK MENANGKAL INTOLERANSI BERAGAMA PADA MAHASISWA - Rahmat, Munawar; Firdaus, Endis; Fahrudin, Fahrudin (Indonesian Community Service and Empowerment Journal (IComSE), 2023)
Various studies have found that around 50% of Indonesian students and university students are intolerant. Other research results show that students are more intolerant of fellow Muslims from different schools of thought. The roots of intolerance are twofold. First, they misunderstand the meaning of believer and disbeliever in the Qurâ€™Än. Second, they misunderstood the basics of other religions and schools of thought. The training aims to provide digital thematic methods of the Qurâ€™Än to build substantive religiosity and religious tolerance for PAI tutors. The training method uses lectures, questions and answers, discussions, demonstrations, implementation exercises, and small group guidance via zoom. The training participants were 50 prospective PAI tutor students. The training was successful because most of the participants: First, they were able to implement the Thematic digital Qur`Än method; second, looking at the meaning of believing-unbeliever refers to good and evil characters, not referring to religious identity; and third, to better understand the implications of religion directly from the Qurâ€™Än in a substantive and tolerant manner.